Pengaruh Penyerbukan Terhadap Produksi Buah Naga Merah (Hylocereus polyrhizus) - Sri Hadiati; Umjunidang Umjunidang (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2019)
This study aims to determine the effect of pollination on production of red dragon fruit. The study was conducted from January 2017 to May 2017 at the Aripan Experimental Field, Indonesian Tropical Fruit Research Institute. The treatments used were open pollination and hand cross pollination on 3 accessions of red dragon fruit (Hylocereus polyrhizus) (Sabila Merah, HP-Lbs, HP-01). The number of crosses of each treatment ranged from 20-30 flowers. The results showed that the hand cross pollination on dragon fruit affected the fruit set, fruit weight, fruit length, fruit grade percentage, but did not affect the total soluble solid (TSS) of fruit. HP-01 accession had a percentage of fruit set, fruit weight, fruit length, TSS, and percentage of super and A fruit grade were relatively the same between the hand cross pollination and open pollination. Only several accessions of Hylocereus polyrhizus need hand cross pollination. Keywords : Hylocereus polyrhizus, pollination, production